2014
DOI: 10.4103/2229-5178.137778
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of contact allergy to dental materials by patch testing

Abstract: Background:Dental products are widely used by patients and dental personnel alike and may cause problems for both. Dental materials could cause contact allergy with varying manifestations such as burning, pain, stomatitis, cheilitis, ulcers, lichenoid reactions localized to the oral mucosa in patients, and hand dermatitis in dental personnel. Patch testing with the dental series comprising commonly used materials can be used to detect contact allergies to dental materials.Aim:This study aimed to identify conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
1
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 23 publications
2
27
1
6
Order By: Relevance
“…A signifi cant new study emerged that investigated contact allergy among dental personnel and patients with oral disorders who had come in contact with these materials 34 . Research in dental personnel with a history of hand dermatitis (patch testing) showed multiple allergies to various dental materials, and multiple standard allergens (N , N-dimethyl-p-toluidine, 2 hydroxy-4-methoxybenzophenone, methylhydroquinone, nickel sulfate, copper sulfate, palladium, methyl methacrylate, ethylene glycol dimethacrylate, and 1,4-butanediol dimethacrylate) 34 . Among other signifi cant reactions, allergic CD caused by acrylates and methacrylates stands out for causing occupational and non-occupational allergic CD.…”
Section: Reactions To Other Substancesmentioning
confidence: 99%
“…A signifi cant new study emerged that investigated contact allergy among dental personnel and patients with oral disorders who had come in contact with these materials 34 . Research in dental personnel with a history of hand dermatitis (patch testing) showed multiple allergies to various dental materials, and multiple standard allergens (N , N-dimethyl-p-toluidine, 2 hydroxy-4-methoxybenzophenone, methylhydroquinone, nickel sulfate, copper sulfate, palladium, methyl methacrylate, ethylene glycol dimethacrylate, and 1,4-butanediol dimethacrylate) 34 . Among other signifi cant reactions, allergic CD caused by acrylates and methacrylates stands out for causing occupational and non-occupational allergic CD.…”
Section: Reactions To Other Substancesmentioning
confidence: 99%
“…Contact sensitivity to systemically administered drugs in HCW is mostly caused by antibiotics such as penicillins, cephalosporins and aminoglycosides 54,55 and can be due to inadvertent contact with drug solutions for parenteral administration or, occasionally, by allergens in aerosols preparations or from the powder of pills crushed to administer to patients with swallowing problems. 54,55 In dental HCW we found, as expected, sensitization to (meth)acrylates used in dental procedures, as prosthodontic restorations, 57 but most cases of (meth)acrylate allergy were related with the use of artificial nails or long lasting acrylate nail varnish, 2,58 a procedure still allowed in our HCW. Our study emphasizes the importance of patch testing in HCW, to identify the allergens and orient eviction in each individual case, which, as previously reported was associated with a relatively good outcome.…”
Section: Discussionmentioning
confidence: 63%
“…Oral mukozada ağrı, yangı gibi şikayetler ile başvuran hastalarda stomatit, keylit, bukkal mukoza, damak ve dudaklarda lokalize likenoid lezyonlar görülebilir 9 . Bazı yazarlar intolerans sendromu olarak tanımladıkları tabloda; dental materyal ile ilişkili semptomu olan hastalarda dental yama testi pozitifliğini ve dental restorasyonun uzaklaştırılması ile birlikte semptom ve bulgularda düzelme olması şartını aramaktadırlar 10 .…”
Section: Discussionunclassified
“…Oral kavitede yer alan amalgam, zaman içerisinde gelişen korozyon ve metal iyonlarının salınımı ile duyarlanmaya ve ardından tip 4/gecikmiş hipersensitivite reaksiyonlarına neden olmaktadır 12 . Civa, oral mukozadaki likenoid lezyonlarda bugüne kadar en sık bildirilen alerjen olup; bakır, krom, nikel, palladyum ve altın sık rastlanan diğer alerjenler arasındadır 9 . Hosoki ve ark.…”
Section: Discussionunclassified